2019
DOI: 10.1186/s12931-019-1072-4
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of vitamin D and lung function in patients with asthma

Abstract: Background There is growing literature suggesting a link between vitamin D and asthma lung function, but the results from systematic reviews are conflicting. We conducted this meta-analysis to investigate the relation between serum vitamin D and lung function in asthma patients. Methods Major databases, including OVID, MEDLINE, Web of Science and PUBMED, were searched until 10th October 2018. All published observational studies relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 65 publications
(58 reference statements)
2
32
0
3
Order By: Relevance
“…Also in smokers, we observed a similar relationship with lung function markers. Similar to our findings, a meta-analysis on 27 studies suggested that serum 25(OH)D concentration was directly associated with lung function in asthma patients 31,32 . Another study conducted on 2,607 adolescents aged 15 years found that serum 25(OH)D concentrations were directly associated with FVC and FEV 1 .…”
Section: Discussionsupporting
confidence: 91%
“…Also in smokers, we observed a similar relationship with lung function markers. Similar to our findings, a meta-analysis on 27 studies suggested that serum 25(OH)D concentration was directly associated with lung function in asthma patients 31,32 . Another study conducted on 2,607 adolescents aged 15 years found that serum 25(OH)D concentrations were directly associated with FVC and FEV 1 .…”
Section: Discussionsupporting
confidence: 91%
“…Pulmonary, blood pressure, and other effects Additionally, from the VIDA trial, central blood pressure was significantly reduced in patients taking vitamin D supplementation (−7.5 mmHg, p = 0.03), (157) and the number of patients taking NSAIDs was significantly reduced (RR, 0.87, p = 0.01). (158) Furthermore, giving vitamin D to the normal population and to the vitamin D-deficient population improves lung function, (159) in line with a meta-analysis, (160) as well as reducing age-related bone loss. (161,162) In an individual participant data meta-analysis of 15 RCTs, daily or weekly supplementation in individuals with vitamin D deficiency, defined as a serum 25OHD level <10 ng/ mL, reduced risk of acute respiratory infection by 30% (odds ratio, 0.30; 95% CI, 0.17-0.53).…”
Section: Diabetes Mellitusmentioning
confidence: 82%
“…Median (first-third quartile), n (%) Although observational studies showed a low level of vitamin D level in children with asthma, however, experimental studies on vitamin D supplementation in asthma in children showed conflicting evidence. [13][14][15][16] Therefore, the conventional concept of vitamin D therapy in asthma may work by its immunogenic effect is still controversial.…”
Section: Resultsmentioning
confidence: 99%